2015
DOI: 10.3892/or.2015.3720
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Annexin A1 promotes cellular invasion in triple-negative breast cancer

Abstract: Abstract. Annexin A1 (ANXA1) is a calcium-dependent phospholipid-linked protein, involved in anti-inflammatory effects, regulation of cellular differentiation, proliferation and apoptosis. While many studies have investigated the ANXA1 expression in various tumor types, the role of ANXA1 is not fully understood. Therefore, in the present study, we evaluated the ANXA1 expression in 211 breast cancer patients and compared the levels with clinicopathological factors. ANXA1 was positively expressed in 31 (14.7%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 39 publications
3
45
0
Order By: Relevance
“…Previous reports suggest that ANXA1 is involved in membrane aggregation, cell matrix interaction, vesicle transport, phagocytosis, proliferation, apoptosis, inflammation and cell transformation29. ANXA1 expression is up-regulated in breast cancer30, hepatocellular carcinoma31, melanoma32, and rectal cancer, but down regulated in nasopharyngeal carcinoma33 and cervical cancer34. In breast cancer, ANXA1 expression is associated with BRCA1/2 mutations35.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggest that ANXA1 is involved in membrane aggregation, cell matrix interaction, vesicle transport, phagocytosis, proliferation, apoptosis, inflammation and cell transformation29. ANXA1 expression is up-regulated in breast cancer30, hepatocellular carcinoma31, melanoma32, and rectal cancer, but down regulated in nasopharyngeal carcinoma33 and cervical cancer34. In breast cancer, ANXA1 expression is associated with BRCA1/2 mutations35.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the expression of individual annexins has been associated with breast cancer development and poor prognosis, and modulation of calcium signaling by p53 has been associated with lack of sensitivity to chemotherapy and radiotherapy [20, 22, 27, 45–49]. Pre-clinical validation of prognostic gene candidates in a large independent cohort is a prerequisite for the development of robust biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…However the literature on dysregulation of annexin protein expression in breast cancer is contentious. Deregulation of individual annexins and S100A proteins have been associated with malignant transformation [2226], tumor invasion [2729], metastasis, angiogenesis and drug resistance [20, 30, 31], the effect being dependent on breast cancer sub-type.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ectopic expression of ANXA1 is thought to drive various cancer developments 2,3) . We previously reported that a breast cancer case of positive ANXA1 expression by immunohistochemical (IHC) staining was frequently identified in triple-negative breast cancer (P = 0.007) and was associated with positive venous invasion (P = 0.028) 4) . We also reported that ANXA1 enhanced breast cancer invasion and metastasis under hypoxia in in vitro cell experiments, indicating that ANXA1 was apparently associated with breast cancer progression 4) .…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that a breast cancer case of positive ANXA1 expression by immunohistochemical (IHC) staining was frequently identified in triple-negative breast cancer (P = 0.007) and was associated with positive venous invasion (P = 0.028) 4) . We also reported that ANXA1 enhanced breast cancer invasion and metastasis under hypoxia in in vitro cell experiments, indicating that ANXA1 was apparently associated with breast cancer progression 4) . In addition, we stated that colon cancer cases with positive ANXA1 expression by IHC staining were associated with lymphatic invasion (P = 0.011), venous invasion (P = 0.023), and lymph node metastasis (P = 0.042) 5) .…”
Section: Introductionmentioning
confidence: 99%